A consumer–food security nexus framework analysis for resilient agrifood value chains - Ellis, Emmanuella; Kwofie, Ebenezer Miezah; Ngadi, Michael (AKADEMIYA2063, 2021)
There is a global consensus that the current food system, involving the production, processing, transport, and consumption of food, is failing—threatening our food security, nutritional security and health, social justice, and natural resources—and therefore requires an immediate transformation if the global “zero hunger by 2030” agenda is to be achieved (HLPE 2017; HLPE 2020). The United Nations Committee on World Food Security defines “food security” as the state in which “all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food that meets their food preferences and dietary needs for an active and healthy life” (FAO 2002, Glossary). Food security is increasingly under threat: a report on global food security crises shows that 108 million people from 48 countries suffered from acute food insecurity in 2016 (FAO 2017). By the end of 2019, the number had increased to 135 million in 55 countries (FSIN 2020). By the end of 2020, the impacts of the COVID-19 pandemic had nearly doubled this number to 265 million people (WFP 2020).